E-commerce Website Development Using Scrum Methods on Small Business - Anita Wulansari; Dhian Satria Yudha Kartika; Agussalim; Seftin Fitri Ana Wati; Eristya Maya Safitri; Anindo Saka Fitri (International Journal of Computer, Network Security and Information System, 2022)
Websites are viewed primarily as a platform from which SMEs can portray a sophisticated image and advertise/market their products. One of the main factor affect the adoption of e-commerce by SMEs is the enviroment influence. On small business, the process of recording orders and sales transactions was done manually. These lead to customers complaints because they have to wait for a long time to get the product. In addition, the owners of small business find it difficult to know the popular products among customers. Moreover, the companys are eager to reach out to potential customers. Therefore, an e-commerce website is required not only as a solution to all these problems but also as a bridge between the business and their customers. The website was developed using the Scrum method. The application development process required three sprints to complete the seventeen product backlogs. The system testing proved the system is running according to its function and is accepted by the user.